PENGELOLAAN PROGRAM KELUARGA HARAPAN (PKH) DI KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Yosa Saputra; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Family Hope Program (PKH) is a policy issued by the Ministry of Social Affairs of the Republic of Indonesia as a form of government's seriousness in accelerating poverty reduction in Indonesia. This program aims to develop social protection system for the poor in Indonesia. As the program seeks to help alleviate the burden of dependents and change the lives of poor families (KM) by providing cash assistance to pay for the need, the program's target is in the designation for Poor Families (KM) who have the conditions as beneficiaries in education and health.The implementation of the Family Hope Program in Tembilahan Sub-district has been running since the last three years. The purpose of this research is to know how the management carried out by the agency responsible for the implementation of Family Hope Program (PKH) in Tembilahan Sub-district Indragiri Hilir Regency and what are the constraining factors in the management of Family Hope Program (PKH) in Tembilahan Sub-district Indragiri Hilir Regency. Theory used is Management theory George R. Terry about the principles of management that is Planning, Organizing, Actuating, and Controlling. The research method is descriptive qualitative to get a clear picture about the management that is done related to the implementation of Family Hope Program (PKH). Data collection techniques used interview techniques, observation, and documentation.Based on the results of research can be known as far as the implementation of this program is running well. Where the implementation procedure has been done in accordance with Standard Operating Procedures in the implementation guidelines PKH, where PKH has four stages of implementation from beginning to end which includes validation, aid distribution, group meetings, and verification. Factors that affect the management of the implementation of this program are socialization and infrastructure facilities where these two factors play an important role in the smooth and successful implementation of this Family Hope Program. Can be concluded that the management related to the implementation of Family Hope Program (PKH) done is good enough.Keywords: Management, Family Hope Program (PKH)